ELUCIDATIVE, AS ONE OF CONSTITUENTS OF FIGHT FOR ECOLOGY OF SOUL - Геник, С. М. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
An author establishes that Ukrainian society is characterized by general social mental instability, by the break of vnoutrishnosouspilnih relations, by tension between the population and state, between elites and the masses, endless conflicts into a political elite. Therefore the elucidative is widely to take all links of life of people, public organizations must interfere in the policy of society, not abandoning to power in this very important activity of monocombustible right.